Preliminary analysis of the historical archives of IUHPST/DHST: a bibliography for the history of history of science - Railienè, Birutè (Circumscribere International Journal for the History of Science, 2016)
As is known, documents are the working materials of historians. For some time, the Committee of Bibliography and Documentation (CBD) of the International Union of History and Philosophy of Science and Technology (IUHPST)/Division of History of Science and Technology (DHST) wondered about the fate of the documents that tell the history of the institutionalization of history of science as an autonomous field of research. A large part of that corpus of documents is deposited at Centre d’Archives en Philosophie, Histoire et Édition des Sciences (CAPHÉS), in Paris. This article describes the extant documents and the initial work of classification and cataloging aiming at making the documents available for future studies on the history of history of science and technology.